KETAHANAN LIMA VARIETAS TANAMAN CABAI RAWIT (Capsicum frutescens L.) TERHADAP INFEKSI TMV (TOBACCO MOSAIC VIRUS) PADA UMUR TANAMAN YANG BERBEDA - Dian Eka Kusumawati; Tutung Hadiastono; Mintarto Martosudiro (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
Diseases caused by TMV (Tobacco Mosaic Virus) on chili is important to notebecause it can cause a loss. Chili varieties are currently circulating in the marketand have not been evaluated resistance to TMV (Tobacco Mosaic Virus).Therefore, research is needed on the effects of the attack TMV (Tobacco MosaicVirus) on the growth, production and resistance to chili varieties such. The initialsymptoms are the same, namely the emergence of a mosaic on the leaves of youngplants, followed by chlorosis due to reduced chlorophyll content of plants forphotosynthesis disturbed then a widespread and causes the leaves begin to showsymptoms of the malformation. Leaves of the plant having malformations (leavesshriveled). The results showed that TMV infection can suppress plant growth anddecrease crop production. Treatment plant inoculation at different ages apparentlysignificant effect on plant growth as well as production plants. Chili plantsinfected with virus at a very young age the rate of plant growth and developmentis inhibited, so the plants will grow abnormally. Based on the parameters used tocalculate the resistance category chili tested against TMV virus showed that thevarieties are very susceptible Sonar and Bara, Cakra susceptible, moderatelyresistant while TM Rawit, Samaru resistant to TMV infection.Keywords: Chili plants, TMV, inoculation, infection and resistance